Antiproliferative Amaryllidaceae alkaloids from the bulbs of Hymenocallis littoralis (Jacq.) Salisb. (May 2022) - Ma, Wenjing; Wang, Siyu; Wang, Yihai; Zeng, Jia; Xu, Jingwen; He, Xiangjiu
Abstract: Seven undescribed Amaryllidaceae alkaloids classified into four types, including the plicamine-type, secoplicamine-type, belladine-type and pretazettine-type, along with another three alkaloids that have not been isolated from plant material and seven known alkaloids, were isolated from the bulbs of Hymenocallis littoralis (Jacq.) Salisb. The structures were elucidated on the basis of various spectroscopic methods (UV, IR, MS, NMR, ECD). The isolated alkaloids were screened for antiproliferative activity against four human tumour cell lines (HepG2, HeLa, SPC-A-1, FaDu) through MTT assay, and some alkaloids exhibited potent cytotoxicity. Meanwhile, cell morphological assessment, flow cytometric analysis, Western blot analysis, clone formation and scratch wound assays were utilized for an undescribed belladine-type alkaloid and two known alkaloids, which had antiproliferative effects on the HepG2 cell line via induction of apoptosis in a dose-dependent manner. A pair of diastereoisomers of Amaryllidaceae alkaloids exhibited significant differences in antiproliferative activity. In addition, the alkaloids also possessed the potential to inhibit tumour cell migration. Graphical abstract: Seven undescribed alkaloids classified into four framework types, along with three undescribed natural unknown alkaloids and seven known alkaloids were isolated from the bulbs of Hymenocallis littoralis. Image 1 Highlights: Seven undescribed Amaryllidaceae alkaloids isolated from Hymenocallis littoralis. The alkaloids were screened for antiproliferative activity against four human tumourtumor cell lines. Some alkaloids significantly inhibited tumour cell growth via the induction of apoptosis.